Palladium Nanoparticles Hardwired in Carbon Nanoreactors Enable Continually Increasing Electrocatalytic Activity During the Hydrogen Evolution Reaction. Issue 22 (29th October 2021) - Aygün, Mehtap; Guillen‐Soler, Melanie; Vila‐Fungueiriño, Jose M.; Kurtoglu, Abdullah; Chamberlain, Thomas W.; Khlobystov, Andrei N.; del Carmen Gimenez‐Lopez, Maria
Abstract: Invited for this month's cover is the group of Maria Gimenez‐Lopez at the University of Santiago de Compostela. The image shows the self‐improving electrochemical activity of palladium nanoparticles hardwired into a graphitic step‐edge for hydrogen production. The Full Paper itself is available at 10.1002/cssc.202101236 . Abstract : "…prolonging the lifespan of highly active metal nanoparticles with limited durability for the sustainable electrocatalytic hydrogen production" This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at 10.1002/cssc.202101236 . View the Front Cover here: 10.1002/cssc.202102198 .